Piero Gobetti: Not Only an Analysis of Italian Affairs - Somenzari, Francesca (European Journal of Multidisciplinary Studies, 2020)
Piero Gobetti (Turin 1901- Paris 1926) has been always considered just as a political writer of Italian affairs, but this amounts to an understatement. In his journals, Gobetti took into account several foreign countries with regard to politics, economy, culture, customs and traditions. In these analysis Gobetti proved to have extensive knowledge of the inland dynamics of each state described.
Keywords: Gobetti, foreign affairs, Socialism, cultural heritage